2022
DOI: 10.3390/cli10010003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Urbanization on Urban Heat Island Intensity in Major Districts of Bangladesh Using Remote Sensing and Geo-Spatial Tools

Abstract: Urbanization is closely associated with land use land cover (LULC) changes that correspond to land surface temperature (LST) variation and urban heat island (UHI) intensity. Major districts of Bangladesh have a large population base and commonly lack the resources to manage fast urbanization effects, so any rise in urban temperature influences the population both directly and indirectly. However, little is known about the impact of rapid urbanization on UHI intensity variations during the winter dry period in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(14 citation statements)
references
References 80 publications
0
12
0
2
Order By: Relevance
“…Urban expansion and the rapid densification of cities accentuate the effect of UHIs, as demonstrated by Rahman et al [17]. In their study, a remote sensing and geospatial tool analysis was carried out in the major districts of Bangladesh, where it was evident that land-use changes by urbanization increased LST in the winter seasons from 3 to 8 • C and a cool pavement-based mitigation proposal (such as the one used in this analysis that decreased the LST by 8 • C) could be used to mitigate the effects of UHI due to urbanization.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Urban expansion and the rapid densification of cities accentuate the effect of UHIs, as demonstrated by Rahman et al [17]. In their study, a remote sensing and geospatial tool analysis was carried out in the major districts of Bangladesh, where it was evident that land-use changes by urbanization increased LST in the winter seasons from 3 to 8 • C and a cool pavement-based mitigation proposal (such as the one used in this analysis that decreased the LST by 8 • C) could be used to mitigate the effects of UHI due to urbanization.…”
Section: Discussionmentioning
confidence: 95%
“…It is estimated that by 2030, approximately 61% of the global population will be living in high-density urban areas [16]. The urbanization process is closely associated with landuse and land-cover changes [17]; as a consequence of this fact, cities' temperatures are expected to gradually increase in accordance with the UHI effect. In theory, average UHI intensity varies from 2 to 4 • C, and the maximum intensity ranges from 7 to 14 • C [8].…”
Section: Introductionmentioning
confidence: 99%
“…The study found that these changes in river morphology led to a degradation of river health and had substantial impacts on flood control. Prior studies have shown that the waterbodies in the urban and rural areas of Bangladesh have been going through a rapid land-use transformation in the last few decades [52][53][54]. According to Mahmood et al [6], encroachment and landfills lead to the narrowing of rivers in Bangladesh, and in recent years, this encroachment rate has increased.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Uddin et al (2020) extensively analyzed the Karnaphuli River's water quality and found poor water quality in 11 locations sampled over three seasons. In addition, Rahman, Rony, et al (2022) revealed the direct and indirect consequences of increasing urban temperatures on the population in major districts of Bangladesh, emphasizing the need for a strong framework to guide urban development and limit expansion into ecologically sensitive areas of the city (Bajracharya & Sultana, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%